Clinical and laboratory characteristics of 1179 Czech adolescents evaluated for antibodies to human adenovirus 36 - Aldhoon-Hainerová, I; Zamrazilová, H; Atkinson, R L; Dušátková, L; Sedláčková, B; Hlavatý, P; Lee, Z P; Kunešová, M; Hainer, V (International journal of obesity (2005), 2014)
BACKGROUND: Human adenovirus 36 (Adv36) is associated with obesity in children. Most prior studies have been small and the association of Adv36 status with markers of metabolic risks has been inconsistent. OBJECTIVES: To determine the prevalence of Adv36 antibodies in different weight categories of adolescents and to evaluate the association of Adv36 infection with anthropometric parameters and cardiometabolic health risks. SUBJECTS AND METHODS: In 1179 Czech adolescents (85 underweight, 506 normal weight, 160 overweight and 428 obese), the following variables were evaluated: anthropometric (body weight, height, body mass index, circumferences, fat mass), blood pressure, biochemical and hormonal (lipid profile, glucose, insulin, liver enzymes, adiponectin) and Adv36 antibodies (enzyme-linked immunosorbent assay). RESULTS: Of the total cohort, 26.5% were positive for Adv36 antibodies (underweight: 22.3%; normal weight: 21.5%; overweight: 40.0% and obese: 28.0%). The odds ratio for Adv36 antibody positivity evaluated vs normal weight was 2.61 for overweight (95% confidence interval (CI): 1.77-3.86, P<0.001) and 1.46 for obesity (95% CI: 1.07-1.99, P=0.016). A significantly higher prevalence of Adv36 infection was observed in female subjects (32.5%) in comparison to male subjects (19.7%; P<0.001). Adv36 positivity of the whole cohort was significantly related to body weight (P=0.042), body mass index (P=0.015), hip circumference (P=0.004), body height z-score (P=0.029), and total body fat (P=0.000) and trunk fat (P=0.000). Adv36 antibody-positive girls demonstrated significantly higher body height (167.8 vs 165.0 cm, P=0.01) and waist circumference (77.0 vs 72.0 cm, P=0.01). Infected adolescents exhibited significantly higher levels of total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C), but lower levels of blood glucose. Liver enzymes were significantly increased only in Adv36-positive boys. CONCLUSION: These results demonstrated an association of Adv36 antibodies with obesity and an even greater association with overweight. Adv36 positivity was related to increased fat mass, levels of TC and LDL-C, but to decreased level of blood glucose. No relation to adiponectin levels was revealed.
Keywords: Triglycerides; Adenovirus E1B Proteins; Cholesterol, LDL; Humans; index tělesné hmotnosti; Body Mass Index; složení těla; lidské adenoviry; Pediatric Obesity; adenovirové proteiny E1B; rizikové faktory; Adenoviruses, Human; Female; ELISA; lidé; Biomarkers; Blood Glucose; Waist-Hip Ratio; mladiství; LDL-cholesterol; Enzyme-Linked Immunosorbent Assay; Disease Susceptibility; náchylnost k nemoci; Peptide Fragments; triglyceridy; biologické markery; ženské pohlaví; krevní tlak; obezita dětí a dospívajících; Male; Adiponectin; Insulin; krevní glukóza; Adolescent; Czech Republic; adiponektin; Odds Ratio; peptidové fragmenty; Body Composition; protilátky virové; poměr pasu a boků; Antibodies, Viral; Česká republika; mužské pohlaví; odds ratio; Blood Pressure; inzulin; Risk Factors